Dubbing and Redubbing Animation: Disney in the Arab World (Altre Modernità, 2016)
Distribution of Disney films and TV products in the Arab world has recently undergone a radical change: since the signing of a large-scale agreement between Al Jazeera and Disney, in 2013, most films and TV series are being dubbed, or redubbed, in Modern Standard Arabic. Contrary to the long-standing tradition of dubbing Disney productions using the Egyptian vernacular variety of Arabic, the eminently written, formal language used for administration and classical education has been introduced as a vehicle for animation dialogue. And not without consistent semantic manipulation.  This article seeks to contextualize this recent shift in dubbing animation in the Arab world, with a view to unveiling its underlying dynamics. The role played by Al Jazeera in reshaping media communication and translation across the Arab world and beyond is also considered, in an attempt to grasp the social, political and ultimately ideological implications of its strategies, as well as its power in significantly orienting traditionally imperialist, Western colossi like Disney. A comparative analysis of the original English TV series Aladdin, its Egyptian dubbed version and MSA redubbing follows, providing evidence for this new trend in audiovisual translation aimed at Arabic speakers the world over.